Uncertainties of S-Parameter Measurements in Rectangular Waveguides at PTB - A. T. Schramm; F. K. H. Gellersen; K. Kuhlmann (Advances in Radio Science)
In this work the determination of measurement uncertainties in scattering parameter measurements for waveguide interfaces ranging from R 100 (WR 90) to R 2.6k (WR 3, WM-864) is presented. For each waveguide band a Thru Reflect Line calibration is performed including uncertainties for calibration standards, cable movement, interface repeatability and the characteristics of the vector network analyzer. For reflection and transmission coefficients, envelopes of uncertainties are determined for magnitude and phase angle respectively. In addition, an experiment on connection (interface) repeatability for R 140 was carried out to systematically investigate the influence of shifting and rotating of waveguide flanges. Translation values in steps of 0.3 mm up to 1.5 mm are examined in simulation as well as measurement. The findings of these investigations can be extended and applied to other waveguide bands.